2021
DOI: 10.3390/plants10102060
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic Effect of Two Mexican Medicinal Plants

Abstract: Type 2 diabetes is a worldwide prevalent disease that is due to a progressive loss of adequate β-cell insulin secretion, frequently against a background of insulin resistance. In Mexican traditional medicine, the therapeutic use of hypoglycemic plants to control the disease is a common practice among type 2 diabetic patients. In the present work, we examined the traditional use of the aerial parts of Eryngium longifolium and the rhizome of Alsophila firma, consumed by people use over the day (in fasting state)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Eryngium longifolium is another of the species used to treat diabetes in Hidalgo, where it is given the name “piñuela”, where the form of use is as an infusion of the dried plant (aerial part) taken throughout the day (“agua de uso”) [ 35 , 36 ]. In addition, its use as a diuretic, emmenagogue, and alexiteric has been reported [ 37 ], similar to Eryngium fluitans [ 38 ].…”
Section: Ethnobotany: Description Distribution and Traditional Usesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eryngium longifolium is another of the species used to treat diabetes in Hidalgo, where it is given the name “piñuela”, where the form of use is as an infusion of the dried plant (aerial part) taken throughout the day (“agua de uso”) [ 35 , 36 ]. In addition, its use as a diuretic, emmenagogue, and alexiteric has been reported [ 37 ], similar to Eryngium fluitans [ 38 ].…”
Section: Ethnobotany: Description Distribution and Traditional Usesmentioning
confidence: 99%
“…A dose-independent hypoglycemic effect has been reported for E. longifolium . Andrade-Cetto et al (2021) [ 35 ] evaluated aqueous (30 and 310 mg/kg doses) and ethanolic (32 and 318 mg/kg doses) extracts of the aerial parts of the plant in hyperglycemic STZ-NA Wistar rats. Previously, the authors determined the basic phytochemical profiles (see next section) and acute toxicity tests, which did not show any physical problems or behavioral changes after oral administration of the maximum dose of 2000 mg/kg body weight (b.w.)…”
Section: Biological and Pharmacological Activitymentioning
confidence: 99%
“…While Metformin inhibits functional and structural damage of renal cells and hypoxia by using AMPK activation, this combination improved oxidative stress conditions and prevented diabetic renal injury ( 5 ). In a more recent study provided by del Cetto ( 54 ), author addressed the problem of impaired hepatic glucose production during gluconeogenesis, which is the main source of fasting hyperglycemia, making it one of the contributors to postprandial hyperglycemia in diabetic patients. The main enzymes in the pathway are G6Pase and FBPase.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The ethanolic extract of E. longifolium was evaluated and it was observed that it inhibited the activity of G6Pase by 75% and FBPase was inhibited 100% with a concentration of 5,000 μg/mL. The presence of rosmarinic and chlorogenic acids, which E. longifolium have as major compounds, were responsible for inhibiting such enzymes, since chlorogenic acid is a weak inhibitor of α-glucosidases and rosmarinic acid has a significant reduction power over G6Pase and FBPase, thus controlling the overproduction of glucose in diabetes ( 54 ). The possibility has been raised that the efficiency of the process is due to the solubility of active polar organic compounds in it, since most of the active polar compounds tend to be extracted with chloroform and ethyl acetate, leaving a very small proportion of remaining compounds in the last fraction ( 28 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…
Diabetes mellitus is a prevalent disease throughout the world, it is due to a progressive loss of adequate insulin secretion [4] in Mexico the use of medicinal plants is a common practice to treat this disease , it is estimated that at least 800 plants are used to treat diabetes in Mexico [9], of which there is very little scientific evidence to support their hypoglycemic activity, therefore, their research is essential, under In this context, this small review aims to provide information that contains, on the one hand, a list of 13 plants (Asteraceae) showing the phytochemicals isolated from hypoglycemic plants belonging to the Asteraceae family and on the other hand, a compilation of data on the Empirical use of 40 plants (Asteraceae) reported in Mexico as hypoglycemic, therefore, it is expected that the plants (Asteraceae) presented here will further broaden the knowledge base information on the various plants available for the treatment of diabetes mellitus.
…”
mentioning
confidence: 99%